Occurrence of Giardia cysts and cryptosporidium oocysts in the Temuan Orang Asli (aborigine) River System - Lim, Yvonne Ai Lian; Ahmad, R.A. (SEAMEO Regional Tropical Medicine and Public Health Network, 2004)
A survey of the river water frequently used by the Temuan Orang Asli (aborigine) indicated that 66.7 of the river water samples were Giardia cyst positive and 5.6 were Cryptosporidium oocyst positive. Although Giardia cysts were detected in samples from all the sites (e.g. upstream, midstream, and downstream), Cryptosporidium was only present in one river water sample taken from downstream from a village. The only sample of upstream water which contained Giardia cysts had a concentration of 0.7 cysts/l. All samples taken from midstream contained cysts with a mean concentration of 9.8 +/- 6.6 cysts/l (range = 1-20 cysts/l). Eighty-three point three percent of the samples collected from downstream contained cysts and 16.7 had oocysts. The average concentration of cysts was 12.9 +/- 16.4 cysts/l (range = 0-44 cysts/l), whereas the oocyst concentration was 0.4 oocysts/l. All river samples tested positive for the presence of E. coli, indicating fecal contamination. The results of this study imply that the river system is contaminated with fecal-oral transmitted parasites. The river water, used by the Orang Asli, is a probable route for Giardia and Cryptosporidium transmission in this community. Long term strategies, incorporating health education regarding personal hygiene, and provision of toilets and the importance of their proper usage, need to be embraced by this community in order to control the spread of these parasites.